Guideline of DouYin Short Video Literacy to Chinese Youth - Kaifu, Guan; Yossakrai, Kanokrat; Buranadechachai, Sukanya (Journal of Dhamma for Life, 2025)
This article mainly aims to 1) study the situation of DouYin short videos literacy to Chinese youth in JiLin Province 2) analyze DouYin short video literacy of Chinese youth people in JiLin Province. 3) propose guidelines to improve the media literacy of young Chinese people on DouYin. The research was mixed method which comprised of quantitative and qualitative research. The research instruments are questionnaire, document, in-depth interview, and non-participation observation. The populations came from Changchun city, JiLin Province’s young people who aged between 18-23 years old. The sample size was 400. Online questionnaire was analyzed by using statistic as percentages, means. The research findings revealed that: (1) Douyin short videos are a key part of youth culture, but the platform often emphasizes entertainment over education, with its recommendation algorithm creating an "information cocoon" that reinforces existing preferences. (2) The DouYin literacy of young people in Jilin Province shows a high dependency on DouYin for entertainment and information, but their literacy in discerning information, managing time, and addressing negative impacts requires improvement. (3)Improving the media literacy of young people in Jilin Province on DouYin requires a comprehensive approach involving platform responsibility, education and guidance, self-management, and family support.